2016
DOI: 10.1101/038299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hybrid asexuality as a primary reproductive barrier: on the interconnection between asexuality and speciation

Abstract: Speciation usually proceeds in a continuum from intensively hybridizing populations until the formation of irreversibly isolated species. Restriction of interspecific gene flow may often be achieved by gradual accumulation of intrinsic postzygotic incompatibilities with hybrid infertility typically evolving more rapidly than inviability. A reconstructed history of speciation in European loaches (Cobitis) reveals that accumulation of postzygotic reproductive incompatibilities may take an alternative, in the lit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 82 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…Previous studies showed that their hybridization produces hybrids both in laboratory and natural conditions (Choleva et al, 2012;Janko et al, 2018). Male hybrids between C. elongatoides and C. taenia are sterile due to the aberrant pairing of their chromosomes (Figure 1) (Dedukh et al, 2020;Juchno and Boroń, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that their hybridization produces hybrids both in laboratory and natural conditions (Choleva et al, 2012;Janko et al, 2018). Male hybrids between C. elongatoides and C. taenia are sterile due to the aberrant pairing of their chromosomes (Figure 1) (Dedukh et al, 2020;Juchno and Boroń, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…15.452483 doi: bioRxiv preprint At least in hybrid asexuals, it appears that the switch from sexual to clonal reproduction involves the modification of conservative gametogenic pathways, which is already occurring in the F1 generation (Lenormand et al, 2016;Neaves and Baumann, 2011;Saura, 2013, 2009). Interestingly, in cases where hybridization leads to aberrant chromosomal pairing and hybrid sterility, the adoption of clonal gametogenesis may partially overcome such conflicts and restore fertility (Figure 1) (Dedukh et al, 2020;Janko et al, 2018;Neaves and Baumann, 2011;Stenberg and Saura, 2013). One example of this is premeiotic endoreplication, which is a widespread gametogenic alteration found among a vast variety of unrelated asexual organisms such as plants, invertebrates and vertebrates (Figure 1) (Stenberg and Saura, 2009; Storme and Geelen, 2013; Suomalainen, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial empirical evidence supporting Dobzhansky-Muller incompatibilities has emerged over the years (Rawson and Burton 2002; Barbash et al 2003; Presgraves 2003; Mack and Nachman 2016). However, obligate parthenogens with hybrid origin have not been explicitly considered under this theoretical framework (but see Janko et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other modes of origin, hybridization is attributed for the largest number of obligate parthenogens by far, with nearly all vertebrate parthenogens having hybrid ancestry (Avise 2015). It is still controversial whether hybridization directly leads to parthenogenesis in the F 1 generation (Kearney et al 2009), as only a few attempts succeeded in generating parthenogenetic F 1 s by crossing identified parental lineages found in nature (e.g., Schultz 1973; White et al 1977; Hotz et al 1985; Janko et al 2018). Also, some obligate parthenogens (e.g., Daphnia ) are backcrosses derived from complex introgression events (Xu et al 2013; Xu et al 2015).…”
Section: Introductionmentioning
confidence: 99%